A highly fertile fluffy allele, fl^Y, which produces macroconidia. - D. D. Perkins; V. C. Pollard (Fungal Genetics Reports, 1988)
In 1964, the FGSC obtained a pale-yellow stock which was listed as ylo-3 (Y234M474) [FGSC no. 902].